Faktor-Faktor yang Mempengaruhi Rendahnya Minat Ibu terhadap Pemilihan Metode Kontrasepsi Jangka Panjang di Desa Kedaton Kecamatan Kedaton - Dewi Mulyati; Siti Aisyah; Reffi Damayanti (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2024)
Contraceptive users in the world according to the World Health Organization (WHO) more than 100 million women use contraception which has effectiveness with hormonal contraceptive users more than and 25% using non-hormonal and contraceptive users in the world in 2019 reaching 89%. In 2020 the number of modern family planning users in urban areas will reach 58% while in rural areas reachs 57%. As many as 82% of Africa's population does not use contraception. Southeast Asia, South and West as much as 43% use contraception. MKJP is a contraceptive tool to delay, space out pregnancies and stop fertility that is used in the long term. The purpose of the study was to determine the relationship between knowledge, education and age with the low interest of mothers in choosing MKJP in Kedaton Village, OKU Regency in 2023. The research method used in this study was quantitative using an analytic survey with a cross sectional approach with the population were 454 mothers who were KB acceptors and the sample were 53 using the Acidental Sampling method. Data analysis used the Chi Square statistical test with a p-value <α = 0.05. The results of this study from 26 respondents with good knowledge 15 (57.7%) chose MKJP p.value = 0.003, from 28 respon Dent of higher education 16 (57.1%) chose MKJP p.value = 0.002, while from 26 respondents who were age of low risk 14 (53.8%) chose MKJP p.value = 0.018. Midwives are expected to educate mothers about the importance of using contraception to space births because it cold be affect the mother'shealth.